2022
DOI: 10.1111/agec.12742
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural diversification, productivity, and food security across time and space

Abstract: This article presents an investigation of agricultural production risk over time and across space and its implications for food security. The econometric approach involves a Quantile Autoregressive (QAR) model and a copula to provide a flexible representation of the distribution of yield risk and its evolution over time and across space. The analysis relies on a two‐step estimation method to evaluate the multivariate yield distribution and its spatial and temporal evolution. Linkages between agricultural produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…The technical change was an important driver of China's agricultural TFP growth, while technical efficiency change played a hindering role in general. Technical change can help reduce the harm of risks, especially climate risks [58]. (2) The spatial variation of China's agricultural Tfpch was significant, with the western, eastern, central and northeast China in descending order.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technical change was an important driver of China's agricultural TFP growth, while technical efficiency change played a hindering role in general. Technical change can help reduce the harm of risks, especially climate risks [58]. (2) The spatial variation of China's agricultural Tfpch was significant, with the western, eastern, central and northeast China in descending order.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies will focus on Chinese spatial differentiation of agricultural potential and explore whether it is positively or negatively correlated with natural conditions, economic factors and so on [56,57]. In addition, combining remote sensing data with statistical yearbooks and taking international trade into consideration in the future can be more convincible [52,58].…”
Section: Limitations and Prospects Of This Studymentioning
confidence: 99%
“…The adoption of farm technologies is connected to downside risk exposure (lower crop failure rate). At the same time, climate change is increasing such risks (Chavas et al, 2022). This question became increasingly relevant for Ukraine as climate change substantially alters the production environment in South Ukraine through lower precipitation rates and higher temperatures, leading to a higher frequency of droughts and crop failure rates in these areas, potentially altering the exit decisions of the local farms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, during the COVID‐19 lockdown and amid economic recovery from the pandemic, food insecurity has risen in many countries, including advanced economies, such as the United States (US) (Tian et al, 2022). Therefore, it has become increasingly important to improve the productivity of food production for the well‐being of human beings, as recent research has found positive associations between productivity and food security (Chavas et al, 2022; Villacis et al, 2022) and between food security and human well‐being (Kornher & Sakketa, 2021).…”
Section: Introductionmentioning
confidence: 99%